Two years analysis of acute poisoning in patients presented to Emergency Department of Ayub Teaching Hospital, Abbottabad - Shazia, Salma; Khan, Muhammad Junaid; Rashid, Haroon ur; Farooq, Amjad; Umair, Muhammad; Syed, Subhan Ullah (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acute poisoning is one of the most common causes of poisoning worldwide and is the fourth leading cause of death. It is either accidental or suicidal and causes a high mortality and morbidity. It is more common in males due to prolonged occupational exposure. The objective of this study is to find the pattern of acute poisoning and its relation with demographic variables in the emergency department of Ayub Teaching Hospital, Abbottabad. Methods: This cross-sectional study was carried out on patients of acute intoxication brought to the emergency department of Ayub Teaching Hospital in the year 2017-18. Data was analyzed by SPSS-16.0 and presented as tables and figures. Chi-square test was applied at 5% level of significance. Results: A total of 76 patients, 48 (63.16%) females and 28 (36.84%) males were included during the period. Mean age was 24.12±9.058 years. Thirty-nine (51.32)% cases belonged to rural areas and 37 (48.68)% were from urban areas. Cases of medicinal poisoning were 25 (32.89%) followed by 19 (25%) cases of organophosphate poisoning. Most cases of poisoning 36 (47.4%) were presented in the night shift. Thirty-one (40.79%) cases were brought to the hospital within 1-2 hours of incident. Cases of intentional poisoning were 51 (67.11%) while 25(32.89%) were due to accidental poisoning. Conclusion: Females within the age group 21-35 belonging to rural areas were more prone to poisoning. The common type of poisoning is medicinal poisoning. Most patients were presented to the emergency in the night shift within 1-2 hours of intoxication. Keywords: Poisoning, Emergency, Alcohol, Organophosphates